Constraining the cross-section of dark matter with giant radial arcs in galaxy clusters. Issue 1 (22nd October 2020) - Vega-Ferrero, J; Dana, J M; Diego, J M; Yepes, G; Cui, W; Meneghetti, M
ABSTRACT: We compare the statistics and morphology of giant arcs in galaxy clusters using N -body and non-radiative SPH simulations within the standard cold dark matter (CDM) model and simulations where dark matter (DM) has a non-negligible probability of interaction (parametrized by its cross-section), i.e self-interacting dark matter (SIDM). We use a ray-tracing technique to produce a statistically large number of arcs around six simulated galaxy clusters at different redshifts. Since DM is more likely to interact in colliding clusters than in relaxed clusters, and this probability of interaction is largest in denser regions, we focus our analysis on radial arcs (which trace the lensing potential in the central region better than tangential arcs) in galaxy clusters that underwent (or are undergoing) a major merger. We find that SIDM produces fewer radial arcs than standard CDM but they are on average more magnified. We also appreciate differences in the arc morphology that could be used to statistically favour one model versus the other.